Impact of seed priming with silicon on growth and yield of maize under water stress - Jahid, Mohammad Rafiq; Datta, Avishek; Kuwornu, John K.M.; Anal, Anil Kumar; AFG Western Basins Water Resources Management Project; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
The experiment carried out at the greenhouse of Agricultural Systems and Engineering field, Asian Institute of Technology, Thailand during 27/11/2016 and 05/04/2017 to find out the impact of seed priming with Si on maize (CP 888 New variety) at different soil moisture levels and different soil types under controlled environment. The experiment consisted two types of soil (clay loam soil and clay soil), three soil moisture levels (100 %, 75 % and 50 % of field capacity) and six rates of Si (0, 0.25, 0.5, 01, 1.5, 02mM) and the experiment was conducted in a randomized complete design with 2{u00D7}3{u00D7}6 factorial designs in tree replications. Result indicated that the Si, moisture and soil type had significant effect on most growth parameters, yield components and grain yield of maize. Water deficiency significantly reduced the yield and growth parameters but addition of Si significantly increased growth parameters, yield components and grain yield in both soils. The highest grain yield was obtained at the doses of 0.25 and 0.5mM of Si at 100 % FC and 75 % FC respectively in clay loam soil. Therefore, the highest grain yield was recorded at the doses of 0.25, 2 and 1.5mM of Si under 100 % FC, 75 % FC and 50 % FC in clay soil. All of the examined attributes were increased by increasing Si under three soil moisture levels. In conclusion, priming seeds with 0.25 of Si increased seed germination percentage and more of the parameters of maize.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Agricultural Systems and Engineering, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2017
Keywords: Plants -- Effect of silicates on; Plants -- Effect of stress on; Silicon in agriculture; Seed treatment